2021
DOI: 10.1002/art.41632
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Systemic Lupus Erythematosus in the United States: Estimates From a Meta‐Analysis of the Centers for Disease Control and Prevention National Lupus Registries

Abstract: Objective. Epidemiologic data on systemic lupus erythematosus (SLE) are limited, particularly for racial/ethnic subpopulations in the US. This meta-analysis leveraged data from the Centers for Disease Control and Prevention (CDC) National Lupus Registry network of population-based SLE registries to estimate the overall prevalence of SLE in the US.Methods. The CDC National Lupus Registry network includes 4 registries from unique states and a fifth registry from the Indian Health Service. All registries defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
121
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 14 publications
4
121
1
1
Order By: Relevance
“…SLE generally affects females of childbearing age range from 15 to 44 years with a ratio of 13:1 in females compared to males [ 2 ]. Center for Disease Control and Prevention reported almost 0.32 million cases of SLE in the USA in 2021 [ 3 ]. Prevalence of SLE is rising, most likely due to an increase in early diagnosis of the disease and improved survival with advancements in disease pathology, diagnosis, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…SLE generally affects females of childbearing age range from 15 to 44 years with a ratio of 13:1 in females compared to males [ 2 ]. Center for Disease Control and Prevention reported almost 0.32 million cases of SLE in the USA in 2021 [ 3 ]. Prevalence of SLE is rising, most likely due to an increase in early diagnosis of the disease and improved survival with advancements in disease pathology, diagnosis, and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19, the disease caused by the novel coronavirus SARS-CoV-2, is an ongoing global pandemic. At this writing (January, 2021), the US has seen more cases than any other country, with more than 20 million reported cases and surpassing 350,000 deaths [ 1 ]. Co-occurring and pre-existing health conditions exacerbate susceptibility to and the severity of COVID-19 infections [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was evident that most SLE patients were females and MAS episodes were also observed in higher numbers in females except in Ahn et al's [16] study where 68% of episodes were reported in females but still a higher percentage (32%) were males. It is known that the female:male ratio in SLE patients is 10:1, but the female:male ratio of MAS in SLE patients in Ahn et al's study was 1.4:1 [1,16]. The combined total numbers of females were 166 to 44 males with a ratio of 3.77 to 1 in seven out of eight studies [14,[16][17][18][19][20][21]; this may point towards males as being an independent risk factor that can lead to MAS in lupus patients.…”
Section: Epidemiologymentioning
confidence: 73%
“…Systemic lupus erythematosus (SLE) is a complex disease with a multitude of presentations and complications making it a notorious mimicker of other disease processes. In the United States, SLE has a prevalence of 73 per 100,000 person-years with women nine times more likely to be affected than men [1]. In addition, the disease is more common in individuals from Africa, followed by Asians and Hispanics, and least common in Caucasians [2].…”
Section: Introductionmentioning
confidence: 99%